High-sensitivity cardiac troponin assays: From improved analytical performance to enhanced risk stratification. (3rd April 2017) - Kozinski, Marek; Krintus, Magdalena; Kubica, Jacek; Sypniewska, Grazyna
Abstract: Implementation of cardiac troponin (cTn) assays has revolutionized the diagnosis, risk stratification, triage and management of patients with suspected myocardial infarction (MI). The Universal Definition of MI brought about a shift in the diagnostics of MI, from an approach primarily based on electrocardiography (ECG) to one primarily based on biomarkers. Currently, detection of a rise and/or fall in concentration or activity of myocardial necrosis biomarkers, preferentially cTns, with at least one value above the 99th percentile upper reference limit (URL), is the essential component for the diagnosis of MI. High-sensitivity cardiac troponin (hs-cTn) assays with their superior analytical performance were designed to further facilitate clinical decision making. The ability of hs-cTn assays to detect measurable cTn concentrations in at least 50% of healthy individuals, along with their improved precision (expressed as coefficient of variation ≤10% at the 99th percentile URL) associated with increased recognition of changing values, leads to enhanced risk stratification of patients with suspected MI, and also enables them to be used as prognostic tools potentially useful in other patient subsets. In this comprehensive review, we aim to integrate updated laboratory and clinical knowledge regarding hs-cTn assays in order to promote their optimal use in daily practice. We primarily focus on the role of hs-cTn assays in patients with suspected MI, discussing recommended diagnostic algorithms and result interpretation. Emphasis is also placed on the release of cTns following myocardial injury, the characteristics of antibodies used in available cTn immunoassays, and analytical performance of hs-cTn assays. In this paper, we also review potential challenges related to the selection of a healthy reference population in determining 99th percentile values, biological variation of hs-cTns, inequality between hs-cTn assays, and outline the current status of cTnI standardization. Finally, we discuss in detail the diagnostic and prognostic value of hs-cTn assays, including non-coronary causes of cTn elevation, the potential benefits and risks of point-of-care testing, and the unjustified skepticism of some clinicians regarding implementation of hs-cTn assays. In everyday clinical practice, hs-cTn assays are an important diagnostic advance, predominantly for patients with non-ST-segment elevation acute coronary syndrome (NSTE-ACS), with suspected non-ST-segment elevation myocardial infarction (NSTEMI). In the NSTE-ACS setting, recently introduced short diagnostic algorithms using hs-cTn assays integrated with careful clinical and ECG assessment were found to substantially reduce the time to final diagnosis, shorten visits to the emergency department and allow earlier safe discharge of low risk subjects. Hs-cTn assays have significantly higher sensitivity and negative predictive value for NSTEMI in comparison to contemporary cTn tests, particularly in early NSTE-ACS presenters. However, due to frequently occurring mild hs-cTn elevations, they are also associated with lower specificity and reduced positive predictive value when compared to previous generations of assays. Our review underscores the need for the education of clinicians and medical laboratory professionals regarding appropriate use and interpretation of hs-cTn assays. Adequate training and clinical experience in using these tests are essential to translate the improved analytical performance of hs-cTn assays into enhanced risk stratification and hopefully better patient outcomes.